The effect of using the Yaker constructivist model on the achievement and retention of geography among female students Intermediate second grade (Journal of the College of Basic Education, 2023)
The teaching methods used today are of a throwaway nature in most subjectsEspecially when teaching geography; As this method has become useless and not compatible with the trendmodern educational; Because of determining its impact on the development of the ability of the student in which his role becomes negative.The researchers found through their experience in the field of teaching that the curricula for social subjectssubject to memorization and memorization of information in the first place; It does not help develop mental skills.The traditional method used in teaching measures the student's ability to retrieve informationAnd remember it, and this contradicts the philosophical view of modern education, which stresses the necessity of developing mental skillsMany students and some teachers of social subjects believe that the issue of constancy and retention of knowledgeScientific is a difficult matter; In the belief of the two researchers, this weakness is due to many reasons, foremost among themTraditional teaching methods without stimulating thinking or developing the student's ability to researchsurvey; Such thinking is necessary to understand and assimilate information and facts. The student is activeinteraction with the educational situation.